Foreign Competition and Wage Inequality. - Neary, J (Blackwell Publishing, 2002)
The author argues that increased foreign competition can affect technical choice and skill differentials even when actual imports do not rise significantly. A model is presented of general oligopolistic equilibrium (GOLE) in which a reduction in import barriers (whether technological or policy-imposed) encourages more strategic investment by incumbent firms. The predictions accord with many of the stylized facts: higher skill premia; higher ratios of skilled to unskilled workers employed in all sectors and throughout the economy; little change in import volumes or prices; and rapid technological progress with rather little change in total factor productivity.